2009
DOI: 10.1590/s1519-566x2009000400017
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota associated with tramp ants in a Brazilian University Hospital

Abstract: -Our aim was to study the fauna of ants in the Hospital Universitário of the Universidade Federal do Triângulo Mineiro, municipality of Uberaba, Minas Gerais State, Brazil, as well as to identify the microorganisms the ants carry and their patterns of resistance to antibiotics. Sterile tubes (traps) containing honey were used to attract the ants. Traps were exposed for 3h, and those which attracted ants were considered the test group, while the ones that did not attract the insects constituted the control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
(14 reference statements)
2
5
0
6
Order By: Relevance
“…The genera identified in the present study have been described in previous investigations on the presence of ants in hospital environments in Brazil [5,6,14,32]. The studies cited revealed that ant diversity in Brazilian hospitals is consistently high [33].…”
Section: Resultssupporting
confidence: 72%
“…The genera identified in the present study have been described in previous investigations on the presence of ants in hospital environments in Brazil [5,6,14,32]. The studies cited revealed that ant diversity in Brazilian hospitals is consistently high [33].…”
Section: Resultssupporting
confidence: 72%
“…Surveys in five Brazilian states indicated that some species are predominant in hospitals, and the occurrence of T. melanocephalum was predominant (TANAKA et al, 2007;TEIXEIRA et al, 2009) (BELEI et al, 2006;COSTA et al, 2006;FOWLER et al, 1993;GARCIA et al, 2011;LISE et al, 2006;MOREIRA et al, 2005;PESQUERO et al, 2008;RANDO et al, 2009;TANAKA et al, 2007;TEIXEIRA et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Maringá, v. 35, n. 1, p. 9-14, Jan.-June, 2013 The inpatient units for adults and children, Intensive Care Units (ICU) for adults and children, as well as nursery, surgical centers, nursing stations, sterilizing rooms, kitchens and laboratories are among the wards with high infestation of ants (COSTA et al, 2006;LISE et al, 2006;MOREIRA et al, 2005;PESQUERO et al, 2008;RANDO et al, 2009;TANAKA et al, 2007;TEIXEIRA et al, 2009). Among them, some units with critically ill patients such as ICU, surgical centers and nurseries, receive a lower flow of people and materials, and have a higher frequency of environmental hygiene, then it was expected a lower index of infestation of ants than observed (BRAGANÇA; LIMA, 2010).…”
Section: Acta Scientiarum Health Sciencesmentioning
confidence: 99%
“…Teixeira et al 16 , em seu estudo sobre a microbiota associada às formigas em um hospital universitário, verificaram que 27,1% das bactérias encontradas em formigas da espécie Tapinoma melanocephalum eram pertencentes ao gênero Staphylococcus spp., dentre as quais, 60% foram resistentes à oxacilina e 100% sensíveis à vancomicina. Dentre as cepas isoladas nesse estudo, as bactérias do gênero Staphylococcus spp.…”
Section: Discussionunclassified